New studies in Deweyan education democracy and education revisited - Kricke, Meike 1982-; Neubert, Stefan 1964- (Routledge, 2020)
"This book examines in detail some of John Dewey's most influential writings by connecting them with contemporary issues, perspectives, controversies and debates. Bringing together scholars from the US and Germany, this volume offers an international perspective on current implications, challenges, and risks of democracy and education in the contemporary world. Written for students and scholars in the fields of education and philosophy, New Studies in Deweyan Education, represents a new, unique and innovative way to of approaching the problems and opportunities of democracy and education then and now"--
Keywords: Dewey, John -- 1859-1952; Erziehungsphilosophie; Dewey, John / 1859-1952 / Influence; Education / Philosophy; Democracy and education; Dewey, John / 1859-1952; Influence (Literary, artistic, etc.); Aufsatzsammlung